Use of the Pessary in the Prevention of Preterm Delivery - Thayane Delazari Corrêa; Ester Gomes Amorim; Jade Aimée Guimarães Tomazelli; Mário Dias Corrêa Júnior (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective The gestational complication most associated with perinatalmortality and morbidity is spontaneous preterm birth with gestational age < 37 weeks. Therefore, it is necessary to identify its risk factors and attempt its prevention. The benefits of the pessary in prematurity are under investigation. Our objective was to analyze the use of the pessary in the prevention of preterm births in published studies, and to compare its efficacy with other methods. Methods Randomized clinical trials published between 2010 and 2018 were selected from electronic databases. Studies on multiple gestations were excluded. Results Two studies were in favor of the pessary as a preventive method, one study was contrary to the method and another two showed no statistically significant difference. Themeta-analysis showed no statistical difference with the use of a cervical pessary in the reduction of births < 37 (odds ratio [OR]: 0.63; confidence interval [95% CI]: 0.38-1.06) and < 34 weeks (OR: 0.74; 95% CI: 0.35-1.57) Conclusion The pooled data available to date seems to show a lack of efficacy of the cervical pessary in the prevention of preterm birth, although the heterogeneity of the studies made comparisons more difficult.